Synthesis of Oxazoline and Oxazole Derivatives by Hypervalent-Iodine-Mediated Oxidative Cycloaddition Reactions; Synthesis; Vol. 52, iss. 16 - Yoshimura A. Akira; Saito A. Akio; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Zhdankin V. V. Viktor Vladimirovich (2020, 2020)
Title screen